The Ways to Enhance Environmental Awareness in Higher Education Institutions in Algeria – An Analytical Theoretical Study - Saliha, Guidoum (Journal of Ecohumanism, 2024)
This study aims to identify the means and mechanisms for developing environmental awareness in higher education institutions, as they are among the most important educational institutions in society. These institutions encompass the elite who will lead society in the future and work to promote and develop it in all fields, including the environmental field. Therefore, the university bears the responsibility of fostering environmental awareness among its members through various means, such as: Teaching environmental education, encouraging student environmental clubs, and supporting the organization of environment-related exhibitions. Organizing conferences, seminars, and lectures, promoting volunteer work, and encouraging research in the environmental field. As a leading institution in society, the university cannot stand as a mere spectator regarding the environment in which we live; it must play an active and positive role in supporting environmental awareness and protecting the environment from various threats.